Estudio de la demanda productiva en la empresa Su Agua - Almeida Flores, Carlos Enith (2017)
The research of the case study is carried out in the company "Su Agua" of the canton Montalvo, (located in the street Guillermo Baquerizo and May 24), offering its products with quality standards under the NTE INEN 2200 standard, in order to to satisfy the needs of its customers, producing at least 3,000 to 4,000 bottles per day, also produce small bottles, gallons, medium sleeves and large covers, to cover a part of the province of Guayas, specifically Duran and the province of Rivers.